SHARING ECONOMY AND CREATING VALUE: BUSINESS MODEL CANVAS (Third Sector Social Economic Review, 2018)
As a general concept the sharing economy structures is that defines the spheres of social trade in which consumers relate to one another in order to create value. Brands like Aribnb and Uber which are the most known all around world has great succsess in the built in categories. It is assumed that  sharing economy players which are increase their number and scope will lead to commercial conversions. Business models are guidelines developed on the principle of creating and distributing value, especially in terms of customer value. Within the scope of this research, it is aimed to discuss the functioning of a company operating in the sharing economy. In this direction a business organization which is operating under the sharing economy in Turkey selected and it is tried to expose the structure and activities with the help of Business Model Canvas. A semi-structured interview was used as a method. Obtained findings were interpreted in 9 dimensions in the model.
Keywords: Sharing; Sharing economy; Collaborative consumption; Canvas Business Model; Value Creating